Analisis Tantangan Bangsa Indonesia Menuju Bonum Communae Perspektif Etika Eudaimonia Aristoteles - Yosef Redemptus Bria; Oktovianus Kosat; Mario Venerial Umbu Zerri (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The value of justice is one of the virtues of Indonesian life contained in the fifth principle of Pancasila. As the main value that sustains the common life, the value of justice receives serious attention from the government. As an institution and forum that has the authority to ensure justice, the government has the responsibility to pursue justice. However, there are always challenges and obstacles that can dwarf the flourishing of justice in this country. The purpose of this research is to review and analyze these obstacles. The object of research is the practice of bonum communae in Indonesia. The main theory used to facilitate the research and as the main reference is Aristotle's concept of eudaimonia ethics. The method used is literature. In this research, it is found that the challenges that always hinder efforts to prioritize bonum communae in Indonesia are the inequality between the poor and the rich, the lack of effective governance in government, the ecosystem crisis that can affect many aspects of life together. The results of this research will be very helpful in understanding the existing obstacles, so that the government and all Indonesian people have a definite reference in an effort to prioritize the common good in state life.